Clinical Characteristics and Outcomes of a High-grade Endometrial Cancer Cohort Treated at Instituto Nacional de Câncer, Brazil - Paulino, Eduardo; Melo, Andreia Cristina de (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2023)
Objective To analyze the outcomes of a cohort of patients with high-risk histologies of endometrial cancer (EC) treated at Instituto Nacional de Câncer (National Cancer Institute, INCA, in Portuguese), in Brazil.Materials and Methods We reviewed the medical records of patients with high-risk histologies of EC in any stage registered at INCA between 2010 and 2016 to perform a clinical and demographic descriptive analysis and to evaluate the outcomes in terms of recurrence and survival.Results From 2010 to 2016, 2,145 EC patients were registered and treated at INCA, and 466 had high-grade histologies that met the inclusion criteria. The mean age of the patients was 65 years, 44.6% were Caucasian, and 90% had a performance status of 0 or 1. The most common histology was high-grade endometrioid (31.1%), followed by serous carcinoma (25.3%), mixed (20.0%), carcinosarcoma (13.5%), and clear cell carcinoma (9.4%). Considering the 2018 Fédération Internationale de Gynécologie et d'Obstétrique (International Federation of Gynecology and Obstetrics, FIGO, in French) staging system, 44.8%, 12.4%, 29.8%, and 12.9% of the patient were in stages I, II, III or IV respectively. Age (> 60 years), more than 50% of myoinvasion, higher stage, poor performance status, serous and carcinosarcoma histologies, and adjuvant treatment were independent factors associated with recurrence-free survival (RFS) and overall survival (OS) in the multivariate analysis.Conclusion The current findings reinforced the international data showing poor outcomes of these tumors, especially for serous and carcinosarcomas and tumors with advanced stages, with shorter survival and high recurrence rates in distant sites, independently of the FIGO stage. Adjuvant therapy was associated with better survival.
Keywords: endometrial cancer; endometrial cancer therapy; endometrial cancer pathology; demographic analysis